Development of o-aminobenzamide salt derivatives for improving water solubility and anti-undifferentiated gastric cancer - Shuang Li; Yanli He; Xuelin Li; Yongxia Xiong; Yan Peng; Chengkun Wang; Linsheng Zhuo; Linsheng Zhuo; Weifan Jiang; Xianzhou Lu; Zhen Wang; Zhen Wang (Frontiers Media S.A., 2023)
Background: Gastric cancer is one of the cancers with wide incidence, difficult treatment and high mortality in the world, especially in Asia and Africa. In our previous work, a novel o-aminobenzamide analogue F8 was identified as an early preclinical candidate for treatment of undifferentiated gastric cancer (IC50 of 0.26 μM for HGC-27). However, the poor water solubility of compound F8 prevents its further progress in preclinical studies.Aim: To improve the water solubility and drug-likeness of F8 via salt formation.Method: Different acids and F8 were reacted to obtain different salt forms. Physicochemical property screening, pharmacokinetic property research, and antitumor biological activity evaluation in vitro and in vivo were used to obtain the optimal salt form with the best druggability.Results: our continuous efforts have finally confirmed F8·2HCl as the optimal salt form with maintained in vitro antitumor activity, improved water solubility and pharmacokinetic properties. Importantly, the F8·2HCl displayed superior in vivo antitumor efficacy (TGI of 70.1% in 75 mg/kg) in HGC-27 xenograft model. The further immunohistochemical analysis revealed that F8·2HCl exerts an antitumor effect through the regulation of cell cycle-related protein (CDK2 and p21), apoptosis-related protein Cleaved Caspase-3, proliferation marker Ki67, and cell adhesion molecule E-cadherin. In addition, F8·2HCl showed acceptable safety in the in vivo acute toxicity assay.Conclusion: Salting is an effective means to improve the drug-like properties of compound F8, and F8·2HCl can serve as a promising therapeutic agent against undifferentiated gastric cancer.